Perlindungan Hukum Terhadap Hak-Hak Tersangka Dalam Proses Penyidikan (Studi Kasus di Polresta Tidore Kepulauan) - Indra Rusdian Lego; Syamsia Suaib; Hakim Hakim (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research focuses on the problem of legal protection of the rights of suspects in the investigation process (a case study at the Tidore Islands Police). The purpose of this research is to find out the legal protection for the rights of suspects in the investigation process and the obstacles faced by investigators in implementing legal protection for the rights of suspects in the investigation process. This type of research is qualitative research using an empirical juridical approach. Methods of data collection by observation, interviews, and documentation. The results of the study indicate that the legal protection of the rights of suspects in the Tidore Islands Police has not been effective because its application is not optimal. There are still suspects' rights that are violated by investigators in the investigation process, namely the suspect's right to be free to provide information (Article 52 of the Criminal Procedure Code), the suspect's right to obtain legal counsel (Article 54 of the Criminal Procedure Code), the suspect's right to contact legal advisors (Article 57 point (1) of the Criminal Procedure Code) ), and the right of the suspect to be visited by clergy (Article 63 of the Criminal Procedure Code). In implementing legal protection of these rights, during the investigation process when examining suspects, investigators experienced obstacles including uncooperative suspects, suspects who lied in giving statements, convoluted suspects during interrogation, and difficulty finding two pieces of valid evidence.